Populasi Serangga Hama di Gudang dengan Penciri Atap dan Lantai yang Berbeda di Empat Pasar Lokal Kecamatan Ilir Timur I, Kota Palembang Sumatera Selatan - Ningrahayu, Seviyanti; Herlinda, Siti; Yulistin, Eka; Setyawati, Anita; Anggraini, Erise; Amelia Herwanti, Andriani; Ilmawan, Kalam; Nabila Adinda, Puspa Gemala; Maryati, Maryati; Carsilladepasha, Al Fath (Seminar Nasional Lahan Suboptimal, 2024)
Ningrahayu, S., Herlinda, S., Yulistin, E., Setyawati, A., Anggraini, E., Herwanti,  A. A., Ilmawan, K., Gemala, P. A. N., Maryati, M., Carsilladepasha, F. A. (2024). Population and storage pest spesies from four local markets with various roofs and floors in sub-district of Ilir Timur I, Palembang South Sumatra. In: Ningrahayu et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang  21 Oktober 2024. (pp. 823–835).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Food products are agricultural goods imported from overseas and held for extended durations in local warehouses, resulting in pest infestations that cause a yield weight loss of 10.73%. This study aimed to ascertain the prevalence of pest insects in warehouses across several markets in Palembang City. The methodology employed in this observation involved sampling, direct field surveys, and identification utilizing the texts "Insects of Stored Grain" and "Insects of Stored Products" by David Rees. The survey results indicated that seven species of barnyard insects were identified in several markets within the Ilir Timur I Sub-district of Palembang. Pest insects from the warehouse, acquired via purposive sampling, were classified as storage pests that infest food products, including: Tribolium castaneum, Sitophilus oryzae, Oryzaephilus surinamensis, Carpophilus dimidiatus, Rhyzopertha dominica, Cryptolestes ferrugineus, and Callosobruchus chinensis. Disorganized storage facilities with concrete roofs and cement flooring exhibited elevated populations of insect pests. Storage utilizing a high-positioned fiber ceiling, and a ceramic floor can diminish the incidence of insect infestations. S. oryzae, the predominant storage pest insect, exhibits the maximum population density in rice commodities. R. dominica was found with the lowest population density. Future research need data regarding the storage conditions.